Telaah Ulang Hak Paksa dalam Perkawinan Islam melalui Pendekatan Fiqh, Munâsib al-‘Illah dan ‘Urf - Moh. Dliya'ul Chaq (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2017)
The provision ijbâr Rights in Islam has become the legal umbrella of forced marriage implementation in a deep-rooted society. The existence of unbalanced understanding and strong indication of the influence of ‘urf. Through fiqh approach, munâsib al-‘illah and ‘urf focusing on review of forced reextrictions in Islamic law, obtained that right ijbâr is actually a safeguard against girls but when it becomes a guardian’s right, it can not be applied because; right of girl in the fiqh salaf takes precedence over the right of guardians as the provisions of guardians ‘adal and the requirements of the guardian of mujbîr; legal images of the nature of girl and nature of children in the study of munâsib al-‘illah with the approach of al-qawâ’id al-fiqhîyah has one point of similarity that ‘illat is immature in sense of not being able to determine mas?lah?ah herself that shows maqâsid avoids girls from danger, and this is difficult to achieve by forced marriage; the basic law of the right of ijbâr is the hadith that ‘illat in hadith it is ‘urf so that the hadith’s validity depends on ‘urf; and deliberation between guardians and girls is the best and praiseworthy way of determining a potential mate.